The application of geotextile and granular filters for PCB remediation. Issue 3 (June 2008) - Kalinovich, I.; Rutter, A.; Rowe, R. K.; McWatters, R.; Poland, J. S.
Abstract : The application of a surface, permeable reactive barrier has been implemented at a remote site in the Canadian Arctic for the remediation of soils and water contaminated with polychlorinated biphenyls (PCBs). The initial barrier system was installed in July 2003. Preliminary work in both the field and the laboratory suggested that geotextiles alone may not be adequate for this particular Arctic barrier system, owing to issues related to survivability (specifically the effects of high UV and freeze–thaw) and clogging. Subsequent field and laboratory work demonstrated that granular materials trapped the majority of PCB-contaminated soil without impeding hydraulic performance; however, fines were escaping. Extensive column testing in the laboratory has shown that a nonwoven geotextile filter can be applied with success with a granular permeable reactive barrier system. This paper presents the results of laboratory experiments and field research used in the design of this barrier system.